Konsep Dan Implementasi Pembelajaran Scientific Kurikulum 2013 - Kartika Wanojaleni (STAI Sufyan Tsauri Majenang, 2021)
Learning curriculum 2013 is competency learning by strengthening the learning process and authentic assessment to achieve competency attitudes, knowledge and skills. Strengthening the learning process is carried out through the scientific approach, which is learning that encourages students to be better able to observe, ask questions and collect data, reason and communicate. In the 2013 curriculum, learning activities are directed at empowering all the potential that students have so that they can have the expected competencies through efforts to grow and develop attitudes, knowledge and skills.Other qualities that must be developed in the curriculum and must be realized in the learning process include: creativity, independence, cooperation, solidarity, leadership, empathy, tolerance and life skills of students in order to shape the character and increase civilization and national dignity. The scientific approach in learning students is taught how to find new knowledge, solve problems, think critically, and create creativity, here students become learning subjects from what they were originally told, to find out for themselves. The scientific approach of students is accustomed to be able to find and create something. Thus the learning process based on the scientific approach can train students' independence so that they can further improve academic and non-academic achievement.